Improving Students' Social Skills through Collaborative-Based Physical Education Learning - Fitri Adifa; Khairul Amri (Siber Nusantara Review, 2024)
This study aims to examine the effectiveness of collaborative-based physical education in enhancing students’ social skills. Using a quasi-experimental design with a pretest-posttest control group, this research involved two classes of junior high school students, one as the experimental group and the other as the control group. The experimental group was exposed to collaborative learning strategies during physical education, while the control group followed conventional methods. Data were collected through questionnaires, observations, and interviews. The findings indicate a significant improvement in the experimental group’s social skills, including cooperation, communication, empathy, conflict resolution, and social responsibility. The average posttest score of the experimental group was notably higher than that of the control group. Qualitative data also supported these results, showing increased student engagement and positive peer interactions. Collaborative-based learning in physical education proves to be a powerful approach not only for improving physical competence but also for fostering essential social values. This method is recommended as an alternative strategy to create a more inclusive and socially engaging learning environment.